Les territoires de l’agrobusiness au Brésil - Denise Elias (Confins)
The transformations that occurred in the Brazilian agricultural activity during the past four decades, had a profound impact on the (re) organization of the Brazilian territory, giving rise to new territorial arrangements. The main objective of this paper is to put some aspects to the debate about new forms of organization and use of Brazilian territory from the processes of diffusion of global agribusiness. The argument is that, in Brazil, a significant part of the changes in the field in the last five decades, due to the restructuring process of agriculture, understood as an exacerbation of the capitalist mode of production in the sector, and the organization of agro-industrial networks, promoting changes in social and technical elements of the agrarian structure. In a few decades, the country is a country predominantly agricultural to one of the ten economies in the world. The effects on production, society and space are many and complex. With all this, the classical location factors are resized, occurring new possibilities for production and hence a real spatial dispersion of production and a reorganization of the territory. Among the main vectors of this reorganization would the spread of global agribusiness. All this results in deepening of the territorial division of labor, a new distribution of production functions, a new economic geography, which culminate in the remodeling of the territory and new spacial for geographical studies. One of these spatial profiles is entirely relevant to analyze the emergence of new territorial arrangements productive resulting sociospatial dynamics inherent in the diffusion of globalized agribusiness, which I am calling the Productive Territory of Agribusiness. These are the territory of agribusiness, chosen to receive the most significant productive investment inherent in the sector. This accentuates the reality refunctioning of agricultural areas and leads to territorial distribution of productive specialization, denoting selectivities are numerous and promoting processes of urban and regional restructuring in different parts of the country. All this results in breaking many of the paradigms that have profoundly marked the social, economic and political country, making the old schemes used to classify the Brazilian urban network and the regional divisions require, in part, of revisions. Thus, among the main objectives of this text highlight: discuss the concept of the Productive Territory of Agribusiness to present the evidence for the identification and characterization of the mentioned region; improve the analytical path that has been trodden and enhance the sense in the context of geographic studies the prospect of a possible consolidation of this conceptual idea.